Comparison of the effects of mitral regurgitation and pulmonary arterial hypertension on left atrial functions - Aksu, Ugur (Annals of Medical Research, 2021)
None
Keywords: Left Atrium; Mitral Regurgitation; Pulmonary Arterial Hypertension; Strain.